Training on Creating Animated Videos for Islamic History Learning for Junior High School Teachers Tanjung Medan Subdistrict Rokan Hilir Regency - Maralottung Siregar; Husni Mubarok; Verawati Verawati; Khairani Alkarimah (International Journal of Community Service Implementation, 2026)
This community service program was designed to enhance the professional competence of junior high school teachers in Tanjung Medan Subdistrict, Rokan Hilir Regency, particularly in the development of animated instructional videos for Islamic History learning. Responding to the growing demand for digitally mediated instruction, the program emphasized the improvement of teachers’ digital literacy and pedagogical creativity in designing interactive learning media. The program was implemented using a systematic training framework comprising three stages: preparation, implementation, and evaluation, and adopted a participatory approach aligned with teachers’ instructional needs. Training activities included theoretical presentations, demonstrations, guided hands-on practice, and continuous mentoring in the use of free and user-friendly animation applications, namely Canva and Plotagon Story. The findings indicate a significant improvement in teachers’ knowledge, skills, and confidence in producing animated learning videos, as evidenced by their active engagement and high level of participation throughout the training sessions. Despite encountering challenges such as limited availability of technological devices and heterogeneous levels of digital competence among participants, the program was positively received and achieved its primary objectives. Overall, the results suggest that sustained professional development initiatives focusing on digital media production are essential for strengthening teachers’ digital competence and enhancing the quality of Islamic History instruction in junior high schools.